Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/vaccines10091564
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Epitope-Based Vaccine Candidate for Monkeypox: An In Silico Approach

Abstract: Currently, there are limited treatment options available for the monkeypox disease. We used a computational strategy to design a specific antigenic vaccine against pathogens. After using various immunoinformatic tools and filters, cytotoxic T-cell lymphocyte (CTL)-, helper T-cell lymphocyte (HTL)-, and interferon gamma (IFN-γ)-inducing epitopes, which comprised the vaccine, in addition to other parameters, such as antigenic and allergic profiles, were assessed to confirm the safety of the vaccine. However, vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…The T cell epitope “ILFLMSQRY” was suggested as the best vaccine candidate in this study based on the antigenicity score, nonallergenic and nontoxic qualities. In our study, the antigenicity of the vaccine candidate was predicted by the VaxiJen 2.0 server to be 1.0469 which is significantly higher than the vaccine candidate studied by Khan et al [ 61 ] and Abdi et al [ 63 ]. Antigenic scores of the selected 3 epitopes for vaccine designing according to the in silico study of Khan et al [ 61 ] were reported to be 0.52, 0.56, and 0.76, respectively.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The T cell epitope “ILFLMSQRY” was suggested as the best vaccine candidate in this study based on the antigenicity score, nonallergenic and nontoxic qualities. In our study, the antigenicity of the vaccine candidate was predicted by the VaxiJen 2.0 server to be 1.0469 which is significantly higher than the vaccine candidate studied by Khan et al [ 61 ] and Abdi et al [ 63 ]. Antigenic scores of the selected 3 epitopes for vaccine designing according to the in silico study of Khan et al [ 61 ] were reported to be 0.52, 0.56, and 0.76, respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…Antigenic scores of the selected 3 epitopes for vaccine designing according to the in silico study of Khan et al [61] were reported to be 0.52, 0.56, and 0.76, respectively. The constructed vaccine studied by Abdi et al [63] had an antigenicity score of 0.685. epitope was found to interact with 4 MHC I molecules including HLA-B * 15:01, HLA-A * 30:02, HLA-A * 03:01 and HLA-A * 32:01. Immune receptor molecules and antigenic molecules must interact for an immune response to be effectively activated.…”
Section: Discussionmentioning
confidence: 99%
“…Epitope prediction appeared in the eyes of vaccine developers as early as the outbreak of MERS-CoV, breaking through the stagnant research and development process and providing new vaccine candidates [ 119 ]. This technology is still in continuous application and development, and has been used in a variety of research and development of specific vaccines in recent years, such as monkeypox vaccine [ 120 ] and orthohantavirus vaccine [ 121 ]. Among them, multi-epitope vaccine is an effective way to deal with the continuous mutation of the virus, which brings good news for the future development of SARS-CoV-2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Since MPXV is so very similar to the smallpox virus, vaccinations and antiviral treatments developed for smallpox can be used successfully against monkeypox. 1,13,14 Cross-immunity against poxviruses, however, has been on the wane worldwide ever since smallpox vaccination campaigns were abandoned. That is why in 2022, when monkeypox broke out in various parts of the world, public health officials began to worry about the possibility of a new global pandemic.…”
Section: Introductionmentioning
confidence: 99%